Answer: y =
![(x + 4)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/sz7lj70ivdc8fi88w8l9325i5odnfsjb0k.png)
Explanation:
Inverse of an equation is to do the complete opposite. So for starters, replace x with y.
You'll end up with x = 3y - 4.
Then, you add 4 to both sides, leaving you with x + 4 = 3y
After, you divide both sides by 3 to get y by itself, so your equation should be y =
![(x + 4)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/sz7lj70ivdc8fi88w8l9325i5odnfsjb0k.png)